PKM Penyuluhan Potensi Desa Wisata Mangrove Pantai Sederhana Melalui Optimalisasi Potensi Mangrove - Jannah, Miftahul; Adi Prasetia, Dian Eko; Aprian, Riska; Kholifah, Vivit Nur (The IMPACT : Jurnal Pengabdian Kepada Masyarakat Universitas Islam As-Syafiiyah, 2024)
The mangrove forest is one of the natural treasures in Pantai Sederhana Village, Muara Gembong Subdistrict, Bekasi Regency. Mangrove plants have been present since ancient times, and their distribution is quite abundant in Pantai Sederhana Village. However, not many people have utilized them. Strategic steps are needed to improve the economic status and address unemployment in Pantai Sederhana's community by developing the abundant mangrove potential in the village. Community service activities aim to enhance understanding of the analysis of mangrove tourism potential and the economic value it holds for the people of Pantai Sederhana Village. The implementation of community service uses counseling methods to facilitate the transfer of knowledge to the community. Counseling activities involve delivering materials and discussions on the potential development of mangrove tourism in the village. The outcome of the community service activity is a counseling session conducted by Universitas Islam As-syafiiyah on August 29, 2023. The counseling utilized presentation and discussion methods to explore the potential of mangrove tourism, covering topics such as optimizing mangrove potential, raising awareness among the community about tourism, and the role of the local government in developing the village into a tourist destination. The participants in the community service included village officials, community leaders, and 25 residents, with the goal of developing the mangrove potential in Pantai Sederhana Village to enhance the economic well-being of the community.